1993
DOI: 10.1177/000841749306000508
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Guidelines for Client-Centred Practice: Impact Study Findings

Abstract: The Guidelines Impact Study investigated use and usefulness of the guidelines for client-centred practice produced in the 1980's by the Department of National Health and Welfare and the Canadian Association of Occupational Therapists. This paper outlines the study, summarizes findings, and discusses implications for revising and updating the Guidelines. Qualitative interview data from key informants across Canada were incorporated into a quantitative survey of a 5% sample of CAOT members. Data reveal variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 2 publications
1
25
0
3
Order By: Relevance
“…Such an individualized collaborative approach is also in line with the literature on learning that we touched upon in the background section. Further it is in line with the call for clientcentered practice that has been so prominent in the occupational therapy literature [15].…”
Section: Identify the Indi6idual Meaning Of The Occupational Problem supporting
confidence: 68%
See 1 more Smart Citation
“…Such an individualized collaborative approach is also in line with the literature on learning that we touched upon in the background section. Further it is in line with the call for clientcentered practice that has been so prominent in the occupational therapy literature [15].…”
Section: Identify the Indi6idual Meaning Of The Occupational Problem supporting
confidence: 68%
“…In a study of therapists' information-processing approaches, Neistadt [14] stressed that it was important to focus on the learning aspects of treatment for older adults with chronic diseases. It has been suggested that the learning that occurs when caring for a relative with dementia provides an especially interesting avenue for further research to support the development of new approaches for caregiver education programs in occupational therapy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, an impact survey (Blain & Townsend, 1993) about the 1983 clinical guidelines on practice (Canadian Association of Occupational Therapists [CAOT] & Department of National Health and Welfare, 1983) suggested that identifying spirituality as a component of the person in a model of occupational performance did not have much effect on occupational therapy practice. The respondents to the survey had mixed interpretations of the spiritual components of the model.…”
Section: Résumémentioning
confidence: 99%
“…Blain and Townsend (1993) surveyed 285 Canadian occupational therapists and found that, compared with mental, physical and sociocultural components, spirituality received the least emphasis in practice. Knox (as cited in Engquist et al, 1997) found that although 98% of Colorado occupational therapists surveyed believed that a person's spirituality can be influenced by illness and disability, only 54% agreed that addressing spiritual issues was within the scope of the occupational therapy profession, and 37% reported being confused about their role in exploring spiritual issues with clients.…”
Section: Scope Of the Problemmentioning
confidence: 99%